E-Commerce as a Mediator of Market Orientation on MSME Performance in Kendari - Abdul Razak; Asraf Asraf; Nofal Supriaddin (Universitas Dharma Wacana, 2022)
The purpose of this study is to test the four hypotheses, namely to partially test and analyze the effect of market orientation, e-commerce on MSME performance, market orientation on e-commerce, and the mediating role of e-commerce on the effect of market orientation on MSME performance in Kendari City. The population in this study were all MSME owners with a sampling technique using proportional stratified random sampling, which is a technique for determining sample size when the population is proportionally stratified. The sample of this study was 100 respondents divided into 10 districts. The analytical method used is multiple linear regression analysis. The results showed that partially market orientation had a positive and significant effect on the performance of MSMEs, market orientation had a positive and significant effect on e-commerce, e-commerce had a positive and significant effect on the performance of MSMEs, and tested the role of e-commerce as a mediating variable in the relationship. market orientation towards the performance of MSMEs resulted that e-commerce as a perfect mediator